Estrategias publicitarias en MCL Comex en la ciudad de Babahoyo, en el periodo 2023. - Moreta De Lucca, Emely Carolina (2024)
The case study entitled "Advertising strategies in the company MCL COMEX in the city of Babahoyo in the period 2023" analyzes the marketing tactics used in the company, which carries out its commercial activity as a courier for parcels and packages, the challenges that it presents are low audience segmentation and little digital presence. To carry out this study, inductive and descriptive methods were used, which revealed the deficiencies that the company currently presents in its advertising area, this determined through an interview with the owner and surveys applied to customers, the results obtained indicated that there is a regular perception of advertising and a lack of brand awareness among customers, which indicates a need to improve segmentation and online presence. It is recommended to carry out more specific and attractive campaigns, improve digital presence and use tools to measure advertising effectiveness. The analysis also highlights the importance of developing a comprehensive digital strategy, including the creation of relevant online content and the use of platforms such as Google Ads and social media to increase visibility. In addition, it is suggested that the company continuously monitor its metrics to adjust its strategies in real time. With these improvements, MCL COMEX will be able to optimize the use of its resources, increase the return on investment in advertising and establish stronger connections with its customers, which will contribute to a better positioning in the competitive market.